Issues of intensive care and liver transplantation tactics in fulminant liver failure - L. U. Agumava; V. A. Gulyaev; K. N. Lutsyk; O. D. Olisov; R. B. Akhmetshin; K. M. Magomedov; B. I. Kazymov; A. R. Akhmedov; K. F. Alekberov; B. I. Yaremin; M. S. Novruzbekov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Fulminant liver failure is usually characterized as severe acute liver injury with encephalopathy and synthetic dysfunction (international normalized ratio [INR] ≥1.5) in a patient without cirrhosis or previous liver disease. Management of patients with acute liver failure includes ensuring that the patient is cared for appropriately, monitoring for worsening liver failure, managing complications, and providing nutritional support. Patients with acute liver failure should be treated at a liver transplant center whenever possible. Serial laboratory tests are used to monitor the course of a patient's liver failure and to monitor for complications. It is necessary to monitor the level of aminotransferases and bilirubin in serum daily. More frequent monitoring (three to four times a day) of blood coagulation parameters, complete blood count, metabolic panels, and arterial blood gases should be performed. For some causes of acute liver failure, such as acetaminophen intoxication, treatment directed at the underlying cause may prevent the need for liver transplantation and reduce mortality. Lactulose has not been shown to improve overall outcomes, and it can lead to intestinal distention, which can lead to technical difficulties during liver transplantation. Early in acute liver failure, signs and symptoms of cerebral edema may be absent or difficult to detect. Complications of cerebral edema include increased intracranial pressure and herniation of the brain stem. General measures to prevent increased intracranial pressure include minimizing stimulation, maintaining an appropriate fluid balance, and elevating the head of the patient's bed. For patients at high risk of developing cerebral edema, we also offer hypertonic saline prophylaxis (3%) with a target serum sodium level of 145 to 155 mEq/L (level 2C). High-risk patients include patients with grade IV encephalopathy, high ammonia levels (>150 µmol/L), or acute renal failure, and patients requiring vasopressor support. Approximately 40 % of patients with acute liver failure recover spontaneously with supportive care. Predictive models have been developed to help identify patients who are unlikely to recover spontaneously, as the decision to undergo liver transplant depends in part on the likelihood of spontaneous recovery of the liver. However, among those who receive a transplant, the one-year survival rate exceeds 80 %, making this treatment the treatment of choice in this difficult patient population.